Strongmen and state authority: a state-in-society approach to understanding the presence of terrorist sanctuaries - Pfannenstiel, Melia T. (Kansas State University, 2015)
The goal of this dissertation is two-fold. First, is to investigate the relationship between the consequences of state failure and terrorist sanctuaries, which is the prevailing explanation in extant literature. Post 9/11 United States counterterrorism policy has focused on the role of the state in providing safe haven or sanctuary to transnational terrorist organizations. However, anecdotal evidence suggests that both weak and strong states host terrorist sanctuaries. Thus, no clear explanation for why transnational terrorist sanctuaries are in some weak and strong states but not present in others currently exists. Second, this dissertation seeks to fill this gap by adopting Migdal’s (1988) state-society interaction approach to explain the presence of terrorist sanctuaries. This dissertation hypothesizes that the role of society’s structure and societal strongmen’s interactions with the state are an important determinant in whether or not transnational terrorist organizations will seek to establish safe haven within a given territory. Sageman’s (2008) hub and node approach on the operational capacities of transnational terrorist sanctuary networks helps to explain differences in types of sanctuaries. Using a newly constructed dataset on terrorist sanctuaries for quantitative analysis and qualitative analysis through case studies, this dissertation intends to show that the presence of terrorist sanctuaries in both weak and strong states can be understood through four state-society interaction typologies. The implications of this study are relevant for policymakers seeking to understand and counter the enduring threat of transnational terrorism across the globe.
Keywords: Terrorism; Terrorist sanctuaries; Terrorist safe havens; State capacityState-society interactions; Political Science (0615)